Identification of rhizome-specific genes by genome-wide differential expression Analysis in Oryza longistaminata - Hu, Fengyi; Wang, Di; Zhao, Xiuqin; Zhang, Ting; Sun, Haixi; Zhu, Ling-Hua; Zhang, Fan; Li, Lijuan; Li, Qiong; Tao, Dayun; Fu, Binying; Li, Zhikang (Springer, 2011)
Rhizomatousness is a key component of perenniality of many grasses that contribute to competitiveness and invasiveness of many noxious grass weeds, but can potentially be used to develop perennial cereal crops for sustainable farmers in hilly areas of tropical Asia. Oryza longistaminata, a perennial wild rice with strong rhizomes, has been used as the model species for genetic and molecular dissection of rhizome development and in breeding efforts to transfer rhizome-related traits into annual rice species. In this study, an effort was taken to get insights into the genes and molecular mechanisms underlying the rhizomatous trait in O. longistaminata by comparative analysis of the genome-wide tissue-specific gene expression patterns of five different tissues of O. longistaminata using the Affymetrix GeneChip Rice Genome Array.A total of 2,566 tissue-specific genes were identified in five different tissues of O. longistaminata, including 58 and 61 unique genes that were specifically expressed in the rhizome tips (RT) and internodes (RI), respectively. In addition, 162 genes were up-regulated and 261 genes were down-regulated in RT compared to the shoot tips. Six distinct cis-regulatory elements (CGACG, GCCGCC, GAGAC, AACGG, CATGCA, and TAAAG) were found to be significantly more abundant in the promoter regions of genes differentially expressed in RT than in the promoter regions of genes uniformly expressed in all other tissues. Many of the RT and/or RI specifically or differentially expressed genes were located in the QTL regions associated with rhizome expression, rhizome abundance and rhizome growth-related traits in O. longistaminata and thus are good candidate genes for these QTLs.The initiation and development of the rhizomatous trait in O. longistaminata are controlled by very complex gene networks involving several plant hormones and regulatory genes, different members of gene families showing tissue specificity and their regulated pathways. Auxin/IAA appears to act as a negative regulator in rhizome development, while GA acts as the activator in rhizome development. Co-localization of the genes specifically expressed in rhizome tips and rhizome internodes with the QTLs for rhizome traits identified a large set of candidate genes for rhizome initiation and development in rice for further confirmation.